Análisis de seguridad informática bajo los estándares ISO 27001 en la Notaría Única del Cantón Alfredo Baquerizo Moreno. - Herrera Palma, Elvis Abel (2023)
This research project was carried out with the aim of analyzing computer security based on the ISO 27001 standard at the notary office in the Alfredo Baquerizo Moreno canton. The present research document was developed through the collection of all types of information, conducting a detailed investigation on various freely accessible websites, scientific articles, graduate theses, sources, and bibliographic documentation available on different digital platforms. The results of the study on the analysis of computer security under ISO 27001 standards at the unique notary office of the Alfredo Baquerizo Moreno canton include the analysis of the implementation of security standards, which will help establish appropriate security policies for the environment of the Unique Notary Office of the Alfredo Baquerizo Moreno canton, as well as being able to promptly identify threats and vulnerabilities and have an action plan for any eventualities related to information security. This research project contributes to strengthening computer security at the Unique Notary Office of the Alfredo Baquerizo Moreno canton by analyzing the implementation of security standards, identifying threats and vulnerabilities, and providing an action plan. Information security has become a critical aspect for protecting sensitive data in the digital age, and this study is an important step toward more effective security management in this entity. The line of research on which this study is based is the development of information systems, communication and business and technological ventures, calculating the analysis in the research subline of data transmission and telecommunications processes.